Computation and complexity in economic behavior and organization - Mount, Kenneth R. (Cambridge University Press, 2002)
This book presents a model of computing and a measure of computational complexity which are intended to facilitate analysis of computations performed by people, machines, or a mixed system of people and machines. The model is designed to apply directly to models of economic theory without requiring analysis of approximations.
Keywords: Economics, Mathematical.; Organizational behavior.; Computational complexity.; Comportement organisationnel.; Complexité de calcul (Informatique); Mathématiques économiques.; BUSINESS & ECONOMICS -- Economics -- Theory.; Computational complexity; Economics, Mathematical; Organizational behavior